Estrategias didácticas y su influencia en el proceso de enseñanza-aprendizaje de niños con problemas de lectoescritura del 6to grado de educación básica de la U.E San José - Díaz Moreno, Disleyne Hipatya (2025)
The objective of this research is about Teaching Strategies and their Influence on the teaching-learning process of children with reading and writing problems in the 6th grade of Basic Education at the U.E. SAN JOSE. Its main objective is to determine the influence of teaching strategies on the teaching-learning process of children with reading and writing problems in the 6th grade of Basic Education at the U.E. SAN JOSE. A mixed-approach research methodology has been used, explanatory type directed to the two variables of the research, with a descriptive - non-experimental design in which research papers, digital or indexed journals, repositories of the different universities of the country, virtual libraries among others were reviewed to collect information on this topic, aimed at a population of 39 students belonging to the sixth grade of basic education parallel "A". With a sample of 39 students, the technique used for data collection is the survey and the instrument used in this research will be the questionnaire of questions. Once the data was collected, they were tabulated, selecting the Excel statistical tool, the results of this research show that the application of didactic strategies had a positive impact on the teaching-learning process of students with reading and writing problems in the 6th grade of Basic Education at the U.E. SAN JOSE. Improvements in academic performance were observed, reflected in an increase in the level of reading comprehension and writing. In addition, an increase in motivation and participation in school activities was identified.